MODEL KEBIJAKAN INDONESIA TERHADAP AUSTRALIA DALAM MELINDUNGI INDUSTRI GARAM NASIONAL (2009-2011) - Khairunnisa "; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describes the model of the policy Indonesia to Australia in protecting national salt industry in 2009-2011. Through trade agreements Indonesia with Australia, namely IAFTA (Indonesia-Australia Free Trade Agreement) which affects the salt industry in the country, so that the salt imports be cheap and easier to done. This is evident from the increasing amount of Indonesian salt imports from Australia in the years 2010 1.621.594 tons and be 2,473,716 tons in 2011.Authors analyze and describe models of Indonesian policy against Australia in protecting national salt industry. The theoretical framework that writer use in this study is the perspective libralisasi by John Satuart Mill, Alexander Hamilton, and Friedrich List, by the theory of trading strategies "strategic trade theory" protecting is given the country based on libralisme by David Ricardo.This study proves that the policy taken by the Indonesian able to protect national salt commodities by reducing and ban the import of salt from Australia thsn processing national salt, comodity so as to meet the national salt consumption. In according theory that writer use, then the government should make policies that put salt as a strategic commodity in Indonesia. Because salt is used by everyone as a necessity, can notreplaced with other commodities and commodities that role-play in the mobilization of the economy.Development the model of policy national salt from policy proteksi become libralisme. By maximizing the national salt industry centers run protection policy properly, then Indonesia will reach sufficiency salt.Keywords: salt commodities, import, protection policies, IAFTA and sufficiency salt